2016
DOI: 10.1183/13993003.00564-2015
|View full text |Cite
|
Sign up to set email alerts
|

NLRP3 inflammasome expression in idiopathic pulmonary fibrosis and rheumatoid lung

Abstract: In this study we investigated the implication of NLRP3 inflammasomes in the pathogenesis of idiopathic pulmonary fibrosis (IPF) and rheumatoid arthritis-usual interstitial pneumonia (RA-UIP).NLRP3 inflammasome activation at baseline and following stimulation with lipopolysaccharide/ATP was evaluated by measuring interleukin (IL)-1β and IL-18 levels released in the bronchoalveolar lavage fluid (BALF) fluid and by cultures of BALF cells. IL-1β and IL-18 levels were significantly elevated in the BALF and BALF mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
61
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(74 citation statements)
references
References 40 publications
5
61
0
Order By: Relevance
“…Specifically, IL-18 protein levels were highly expressed in alveolar macrophages and epithelial cells [70]. Lasithiotaki et al showed that transcriptional levels of inflammasome components, NLRP3 and caspase-1, were elevated in IPF patients when compared to the controls [71]. In addition, NLRP3 inflammasome activation by ATP was significantly increased in alveolar macrophages from IPF patients when compared to the controls [71].…”
Section: The Role Of Inflammasome-dependent Inflammation In Ipfmentioning
confidence: 99%
“…Specifically, IL-18 protein levels were highly expressed in alveolar macrophages and epithelial cells [70]. Lasithiotaki et al showed that transcriptional levels of inflammasome components, NLRP3 and caspase-1, were elevated in IPF patients when compared to the controls [71]. In addition, NLRP3 inflammasome activation by ATP was significantly increased in alveolar macrophages from IPF patients when compared to the controls [71].…”
Section: The Role Of Inflammasome-dependent Inflammation In Ipfmentioning
confidence: 99%
“…Recent studies suggest a role for nucleotide-binding domain and leucine rich repeat containing family, pyrin domain containing 3 (NLRP3) inflammasome activation in lung inflammation and fibrosis (7)(8)(9)(10)(11). The NLRP3 inflammasome is a key signaling platform that is activated by a variety of signals, such as reactive oxygen species (ROS), to produce IL-1b and IL-18 (12).…”
Section: Clinical Relevancementioning
confidence: 99%
“…NALP3 has been widely investigated with respect to immune response over the past several decades, and it is considered to act as a general sensor for cellular stress. In recent years, NALP3 has been found to play important roles in various pathological processes, including diabetes mellitus (22,23), non-alcoholic steatohepatitis (24,25), chronic kidney diseases (26) and IPF (27). Furthermore, an increasing volume of evidence indicates that NALP3 serves as an important factor in organ fibrosis.…”
Section: Discussionmentioning
confidence: 99%